2023
DOI: 10.1038/s41467-023-36320-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a rosiaite-structured high-pressure silica phase and its relation to lamellar amorphization in quartz

Abstract: When affected by impact, quartz (SiO2) undergoes an abrupt transformation to glass lamellae, the planar deformation features (PDFs). This shock effect is the most reliable indicator of impacts and is decisive in identifying catastrophic collisions in the Earth´s record such as the Chicxulub impact. Despite the significance of PDFs, there is still no consensus how they form. Here, we present time-resolved in-situ synchroton X-ray diffraction data of single-crystal quartz rapidly compressed in a dynamic diamond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…A key role in this mechanism is a metastable rosiaite‐structured silica phase, which forms as lamellae with different crystallographic orientations within the host quartz during compression. This phase is not only responsible for the lamellar amorphization of quartz through its collapse to amorphous silica during decompression (Otzen et al., 2023a) but also serves as an intermediate phase for subsequent nucleation of stishovite during compression. We argue that the diffusion of atoms required for transformation is initiated through frictional heating of such lamellae of rosiaite‐structured silica that are prone to shear due to optimally inclined orientations with respect to the compression direction.…”
Section: Discussionmentioning
confidence: 99%
“…A key role in this mechanism is a metastable rosiaite‐structured silica phase, which forms as lamellae with different crystallographic orientations within the host quartz during compression. This phase is not only responsible for the lamellar amorphization of quartz through its collapse to amorphous silica during decompression (Otzen et al., 2023a) but also serves as an intermediate phase for subsequent nucleation of stishovite during compression. We argue that the diffusion of atoms required for transformation is initiated through frictional heating of such lamellae of rosiaite‐structured silica that are prone to shear due to optimally inclined orientations with respect to the compression direction.…”
Section: Discussionmentioning
confidence: 99%
“…It is argued that the process of amorphization includes the formation of a metastable silica polymorph with the rosiaite structure. 3 Rosiaite and its stable counterparts MSb 2 O 6 (M = Cd, Ca, Sr, Ba) are diamagnetic, but metastable transition-metal ana-logues (M = Mn, Co, Ni, Cu) prepared by ion-exchange reactions are magnetic. The trigonal layered phase MnSb 2 O 6 (P3 ˉ1m) shows antiferromagnetic ordering but its magnetic structure is predicted to be incommensurate with the crystal lattice.…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that the process of amorphization includes the formation of a metastable silica polymorph with the rosiaite structure. 3…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, extensive efforts have been dedicated to probing the high-pressure structures of hydrogen-bonded pharmaceutical and energetic materials. 31−36 The transition from phase III to phase I of piracetam has been examined under experimental conditions involving compression of phase III to 0.2 GPa at 443 K. 37 Additionally, the compression of phase II of piracetam within pressure ranges of 0.45−0.70 GPa induced a reversible, single-crystal to singlecrystal transition, resulting in a novel polymorph, phase V. 38 High-pressure isochoric recrystallizations have yielded new forms of 6-azido-7-methyl [1,2,4]triazolo [4,3-b]pyridazine (C 6 H 5 N 7 ). 39 Gao et al confirmed that pressure-induced molecular deformations led to a reduction in molecular symmetry through high-pressure Raman studies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Pressure on a tens of gigapascals scale can induce significant variations in relatively weak interactions and can be harnessed as a potent tool to reveal concealed phenomena that exist under ambient pressure conditions. High pressure has been extensively employed to investigate a diverse array of materials, encompassing metals, semiconductors, superconductors, minerals, and ice. Pressure can effectively elevate the critical temperature for superconductivity. , The pressure-induced emission behavior exhibited by perovskites holds potential applications in pressure sensing. Two distinct categories of materials, pharmaceutical compounds and energetic materials, have garnered escalating scientific attention. In the production of pharmaceuticals, the manufacturing process involves various procedures such as crystallization, milling, freeze-drying, and tabletting. During these processing and formulation stages, pharmaceutical compounds are frequently subjected to pressure, leading to interconversions between solid forms that can impact properties such as efficacy and toxicity. , Hence, the study of pressure plays a pivotal role in the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%